Optimization of Biofiltration Techniques for Reducing Heavy Metal Contamination in Urban Wastewater - Retno Susetyaningsih; Nurul Muyasaroh; Endah Ayuningtyas; Jumiati Jumiati; Muhammad Rizqi Fahreza (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2025)
This study focuses on optimizing biofiltration techniques to mitigate heavy metal contamination in urban wastewater. The increasing presence of heavy metals in wastewater, particularly in urban environments, poses a significant threat to both human health and ecosystem stability. Biofiltration, a natural remediation process utilizing living organisms, has gained attention as an effective method for removing heavy metals from contaminated water. The research combines experimental analysis with a comprehensive literature review to evaluate and enhance the performance of various biofiltration systems. By examining the influence of different variables, such as plant species, soil composition, flow rate, and pollutant concentration, on the efficiency of heavy metal removal, this study provides a broad perspective on the potential applications of biofiltration. Experimental analysis of biofilter setups demonstrated that specific plant-microbe interactions and substrate types significantly enhance the absorption and accumulation of toxic metals. The literature review further supports these findings by summarizing past studies and providing insights into existing biofiltration techniques, their effectiveness, and limitations. The study's findings indicate that optimized biofiltration can serve as a sustainable and cost-effective solution for urban wastewater management. By providing a detailed understanding of how biofilters can be adapted and scaled for urban applications, the research contributes to the development of environmentally friendly wastewater treatment technologies. The results underscore the importance of integrating biofiltration systems into urban water management strategies for improving water quality and reducing environmental pollution.